O matrimónio entre ingenui e libertini e o ataque político na República Romana : o caso de Marco António e Fádia - Valério, João Paulo (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
The present study aspires to establish the connection between the marriage of an ingenuus and a liberta and political invective in the Roman Republic. For this purpose, we’ve turned to the example of Mark Antony and Fadia. Marcus Tullius Cicero is the only source that refers us a iustum matrimonium between Antony and Fadia.